2018
DOI: 10.5455/jtomc.2017.12.151
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival in adult patients with grade II glial tumors

Abstract: Aim: To investigate survival results of patients with low grade gliomas (LGGs) and to evaluate the predictive role of clinico-pathologic prognostic factors on survival. Material and Methods: Between 2003 and 2014, the adult patients with Grade II glial tumors were evaluated retrospectively. Several variables were investigated to find prognostic factors related with the overall survival (OS) and progression-free survival (PFS).Results: This study involved in 124 patients with median 40 (range; 6-132) months fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…Low-grade gliomas are most often found in males (55–60%), while our study showed the opposite [ 4 , 10 , 14 ]. Differences were observed in the pathogenesis and evolution of low-grade gliomas in terms of female and male sex, with some genes having a protective role for one category and a negative prognosis for the other.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Low-grade gliomas are most often found in males (55–60%), while our study showed the opposite [ 4 , 10 , 14 ]. Differences were observed in the pathogenesis and evolution of low-grade gliomas in terms of female and male sex, with some genes having a protective role for one category and a negative prognosis for the other.…”
Section: Discussioncontrasting
confidence: 54%
“…Life expectancy is relatively good, with an average survival rate of 5.6 to 13.3 years [ 1 ]. A number of molecular and constitutional characteristics contribute to this rate: topography, topographic effects, tumor histology, patient age, type of treatment, tumor volume, and patient performance status [ 1 , 2 , 3 , 4 , 5 ]. Another aspect not to be neglected is the potential for malignant transformation of these tumors, which can vary between 25 and 72% of cases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%